Differential role of AHCYL1 gene in tumor plasticity - Budnik, Nicolás (2019)
Malignant reprogramming of cells is responsible for tumor development. During this process stem-like tumor cells that acquired self-renew capacity produce heterogeneity, tumor dissemination, and relapse after cancer therapy. We have previously identified AHCYL1 as a potential regulation target of core transcription factors OCT-4, SOX-2, and NANOG responsible for cell reprogramming. We studied AHCYL1 by analyzing its cellular location and expression levels during cell plasticity events of tumor cells. We used the glioblastoma (GBM) cell line U87 and lung carcinoma (LC) cell line H1299 as in vitro models since brain and lung have the highest Ahcyl1 expression. We cultured these cell lines in a 3D format in DMEM/F12 medium supplied with FGF, EGF, and B27 and compared with 2D format cultured cells with DMEM serum complemented medium. Ahcy1 localization was determined by immunofluorescence assay and cell fractioning followed by western blotting. To generate U87 and H1299 Ahcyl1 knockdown stable lines, three different shRNAs were tested and the expression levels of Ahcyl1 and the core factors were determined by Western blot and RT-qPCR. Stemness potency was evaluated by ELDA assay (extreme limiting dilution analysis). We found that AHCYL1 localizes both in nuclei and cytosol, in addition to a putative processed isoform in nuclei. In 3D cultures, Ahcyl1 expression is differently regulated compared to 2D cultures. Also, in GBM, AHCYL1 expression was significantly increased, in contrast in LC was decreased (p 0.0001 and p 0.05 respectively). In Ahcyl1-depleted LC cells, the core factors expression levels and the stem potency were increased (p 0.05). Altogether, we conclude Ahcyl1 has a key role as a regulator of stem potency and would be dependent on tumor type.